STUDENTS' PERCEPTION OF THE #KABURAJADULU PHENOMENON (CASE STUDY) - Latiffani, Chitra; Yuma, Febby Madonna; Anjani, Anjani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study maps students’ perceptions of the #KaburAjaDulu phenomenon across four aspects: understanding, exposure sources, causal factors, and perceived impacts. The analyzed questionnaire dataset comprises approximately N = 72 respondents. Descriptive results show that most respondents reported being Aware (55.6%) about #KaburAjaDulu; the most dominant initial exposure source was Social media (X, Instagram, TikTok, etc.) (88.9%). Attitudes toward people seeking opportunities abroad tended to be positive, with the 'Support' category reaching 47.2%. In the long run, the most frequently perceived impact was Loss of potential workforce (52.8%). These findings underscore the strong role of social media in shaping perceptions and the ambivalence between global opportunities and the risk of brain drain. Keyword: KaburAjaDulu; perception; phenomenon; students; social media. Abstrak: Penelitian ini menyajikan gambaran persepsi mahasiswa terhadap fenomena #KaburAjaDulu melalui empat aspek: pemahaman, asal paparan, faktor penyebab, dan dampak yang dipersepsikan. Dataset kuesioner yang dianalisis berjumlah sekitar N = 72 responden. Hasil deskriptif menunjukkan sebagian besar responden menyatakan Tahu (55.6%) terhadap isu #KaburAjaDulu; sumber pertama yang paling dominan adalah Media sosial (X, Instagram, TikTok, dll.) (88.9%). Sikap terhadap orang yang mencari peluang di luar negeri cenderung positif dengan kategori 'Mendukung' mencapai 47.2%. Dalam jangka panjang, dampak yang paling sering dipersepsikan adalah Kehilangan potensi tenaga kerja (52.8%). Temuan ini menegaskan kuatnya peran media sosial dalam pembentukan persepsi serta adanya ambivalensi antara peluang global dan risiko brain drain. Kata kunci: KaburAjaDulu; fenomena; mahasiswa; persepsi; social media.